2007
DOI: 10.1007/s00216-007-1185-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of speciation parameters of Cu, Pb, Cd and Zn in model solutions of Suwannee River fulvic acid by pseudopolarography

Abstract: There is a growing awareness of the importance of quantitative determinations of speciation parameters of the trace metals Cu, Zn, Cd and Pb in aqueous samples containing chemically heterogeneous humic substances, especially when they are present together, interacting with one another and competing for specific binding sites of the humic substances. Such determinations require fundamental knowledge and understanding of these complex interactions, gained through basic laboratory-based studies of well-characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
3
19
1
4
Order By: Relevance
“…Peak height and peak area were recorded in this work. The ratio of peak area-to-height for Pb(II)-SRFA was relatively constant across the range of the deposition potentials used in this experiments as was reported in our recent publication (Chakraborty et al 2007). In this work, peak heights were used in all calculations.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Peak height and peak area were recorded in this work. The ratio of peak area-to-height for Pb(II)-SRFA was relatively constant across the range of the deposition potentials used in this experiments as was reported in our recent publication (Chakraborty et al 2007). In this work, peak heights were used in all calculations.…”
Section: Resultssupporting
confidence: 74%
“…It was reported in our recent study (Chakraborty et al 2007) that a comparison of the heterogeneity parameters (Γ ) for Zn(II),Cd(II), Pb(II) and Cu(II) complexes in the model solutions of SRFA showed that Γ Cd > Γ Zn > Γ Pb > Γ Cu , suggesting that SRFA behaved as a relatively more homogeneous complexant for Zn(II) and Cd(II), whereas it behaved as a relatively more heterogeneous complexant for Pb(II). It was also found (Chakraborty et al 2007) that the order of stability of M-SRFA complex is typically K* Cu >K* Pb >K* Zn >K* Cd .…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…A interpretação dos dados de titulação de um sistema altamente heterogêneo levou à definição do parâmetro de equilíbrio diferencial (K DEF ) dado pela média aritmética ponderada das constantes de equilíbrio condicionais K j para todos os sítios do tipo j envolvidos na complexação (Buffle 1988;Pinheiro, Mota et al 1994;Chakraborty, Fasfous et al 2007). (Pinheiro, Mota et al 1994):…”
Section: Funções Diferenciais De Equilíbriounclassified